Kinerja Pelayanan Dan Rehabilitasi Kesejahteraan Sosial Di Dinas Sosial Kota Bekasi - Fikri Emsa; Zaenuri Khairul Anwar (Department of Public Administration, 2019)
This research is motivated by not achieving the performance targets of the City Social Services so that this study aims to analyze the performance of social welfare services and rehabilitation programs in the Bekasi City Social Service. The research method used in this study is a qualitative approach to the type of descriptive research. In conducting data collection, this study uses interview, observation, and documentation techniques. Then for the data analysis technique that is done is with three different types of activities consisting of reduction, data models, and drawing conclusions. Based on the results of the study, it shows that the performance of the Bekasi City Social Service is quite good but it is still considered to be less than optimal and must be improved again. There are several factors that affect the sub-optimal performance of the Bekasi City Social Service in carrying out social welfare rehabilitation and service programs. To achieve optimal results, it is necessary to have a review of the readiness of the resources (budget, professional workforce, and other materials) in the Bekasi City Social Service.